HUBUNGAN KEJADIAN BULLYING DENGAN KEMAMPUAN INTERAKSI SOSIAL PADA REMAJA DI KELURAHAN KLEAK LINGKUNGAN I KOTA MANADO - Diane Natalia Siswojo; Wenda Merrychrist Oroh; Ferlan Ansye Pondaag (Universitas Sam Ratulangi, 2022)
Background: Social interaction is a social process that occurs in all human life, but the individual's social interaction capabilities including teenagers sometimes decreased due to the situation that can not be faced as never experienced bullying that can provide long-term impact on the victims of bullying. Â Purpose: To find out the incidence Bullying Relationships With Social Interaction Capability in Kelurahan Kleak, Environment 1 Manado. Method This study used a cross sectional study design, using the chi square statistical test. Samples were taken technique is purposive sampling with a total of 78 adolescents. Results a total of 48 adolescents aged 15-18 years. Based on gender, the respondents were predominantly female teenagers. Chi square test analysis shows that Value = 0.201, which means that the two variables are not significantly related.. The In this study, it is known that adolescents who experience bullying in the high category can still have a level of social interaction ability in the good category. Conclusion: community of nursing services can assist in overcoming psychosocial behavior among adolescents to reduce or avoid the adverse effects of bullying incidents on adolescents social interaction skills.Keywords: Bullying Incident;Social Interaction Ability;Adolescent.